Elevated CO2 differentially mitigates chromium (VI) toxicity in two rice cultivars by modulating mineral homeostasis and improving redox status. (November 2022) - AbdElgawad, Hamada; Sheteiwy, Mohamed S.; Saleh, Ahmed M.; Mohammed, Afrah E.; Alotaibi, Modhi O.; Beemster, Gerrit T.S.; Madany, Mahmoud M.Y.; van Dijk, Jesper R.
Abstract: Chromium (Cr) contamination reduces crop productivity worldwide. On the other hand, the expected increase in the future CO2 levels (eCO2 ) would improve plant growth under diverse growth conditions. However, the synergetic effect of eCO2 has not been investigated at both physiological and biochemical levels in Cr-contaminated soil. This study aims to analyze the mitigating effect of eCO2 on Cr VI phytotoxicity in two rice cultivars (Giza 181 and Sakha 106). Plants are exposed to different Cr concentrations (0, 200 and 400 mg Cr/kg Soil) at ambient (aCO2 ) and eCO2 (410 and 620 ppm, respectively). Unlike the stress parameters (MDA, H2O2 and protein oxidation), growth and photosynthetic reactions significantly dropped with increasing Cr concentration. However, in eCO2 conditions, plants were able to mitigate the Cr stress by inducing antioxidants as well as higher concentrations of phytochelatins to detoxify Cr. Notably, the expression levels of the genes involved in mineral nutrition i.e., OsNRAMP1, OsRT1, OsHMA3, OsLCT1 and iron chelate reductase were upregulated in Cr-stressed Giza 181 plants grown under eCO2 . Mainly in Sakha 106, eCO2 induced ascorbate-glutathione (ASC/GSH)-mediated antioxidative defense system. The present study brings the first ever comprehensive assessment of how future eCO2 differentially mitigated Cr toxicity in rice. Graphical abstract: Image 1 Highlights: Cr exposure induces severe oxidative damage and dysregulates mineral homeostasis. ECO2 upregulates the expression of mineral transporter genes in Cr-stressed plants. ECO2 modulates the antioxidant defense and metal detoxification systems. Cultivar-specific responses to the coexistence of Cr and eCO2 will be noticed.